Management of children and adults with all stages of nodular lymphocyte predominant Hodgkin lymphoma — All StAGEs: A consensus‐based position paper from the Hodgkin lymphoma subgroup of the UK National Cancer Research Institute. (1st April 2022) - Shankar, Ananth; Hall, Georgina W.; McKay, Pam; Gallop‐Evans, Eve; Fielding, Patrick; Collins, Graham P.
Summary: A consensus statement for the management for patients of all ages with all stages of nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) — All St AGE s — is proposed by representatives of the UK National Cancer Research Institute (NCRI) Hodgkin lymphoma study group and the Children's Cancer & Leukaemia Group. Based on current practices and published evidence, a consensus has been reached regarding diagnosis, staging and risk‐ik7 stratified management which includes active surveillance, low‐ and standard‐dose immunochemotherapy and radiotherapy.